Role of Perceived Importance in Intergroup Contact. [article]. - van Dick, Rolf.
Furthering G. W. Allport's (1954) contentions for optimal contact, the authors introduce a new construct : the perceived importance of contact. They proposed that perceived importance is the best proximal predictor of contact's reduction of prejudice. If individuals have opportunities for contact at work or in the neighborhood, their chances to have intergroup acquaintances and friends increase. Intergroup contact among acquaintances and friends can be perceived as more or less important, which in turn determines intergroup evaluations. A 1st study shows that the new measure of perceived importance is indeed distinct from established quantity and quality indicators. The results are cross-validated in a 2nd study that also sheds light on the meaning of importance. In 3rd and 4th studies, structural equation analysis and a meta-analysis support the hypotheses. -- (from the author)
Keywords: Psychology-Periodicals.